Proof of concept for molecular velcro based on the attractive interaction between porphyrin and pyridine containing copolymers - M. Sievers; J. C. Namyslo; F. Lederle; E. G. Huebner (eXPRESS Polymer Letters)
In this short communication, we investigated the synthesis and mixing of porphyrin and pyridine functionalized copolymers as a proof of concept for a velcro-like interaction. A functionalized porphyrin monomer with one polymerizable side chain was synthesized following a rational synthetic pathway. Subsequent copolymerization and careful removal of residual free porphyrin led to poly(n-butyl acrylate-co-5,10,15-triphenyl-20-(3-vinylphenyl)porphyrin). The immobilized porphyrin was transformed into the corresponding zinc(II) complex, which is capable of the coordinative binding of one pyridine moiety. Complete metallation was proven by absorption spectroscopy. 4-Vinylpyridine was immobilized by copolymerization with n-butyl acrylate, too. Via controlled radical polymerization conditions, the molecular weight of poly(n-butyl acrylate-co-4-vinylpyridine) was limited to one tenth of the molecular weight of the porphyrin containing copolymer. This large difference in the molecular weight easily allowed identifying the polymers in the mixture of both. With the help of diffusion ordered nuclear magnetic resonance spectroscopy, the complete and temperature-stable precipitation of the porphyrin containing copolymer was observed, proving the expected attractive interaction and supramolecular network formation.